Perioperative and survival outcomes of laparoscopic radical cystectomy for bladder cancer in patients over 70 years - Fontana, Pamela Portella (Cent European J Urol, 2015)
INTRODUCTION: Radical cystectomy in elderly patients is a controversial issue that has noticed an increase in importance overtime because of the lengthening average life span. Our objective was to determine if there were significant differences in the perioperative outcomes of patients over 70 years with bladder cancer treated with laparoscopic radical cystectomy (LRC) compared to those of younger patients. MATERIAL AND METHODS: We selected 180 patients who underwent LRC in our department in the period between 2005-2012. We divided them into 2 groups: 57% <70 years and 43% >70 years, and we compared the different parameters such as: comorbidities, intraoperative and post-operative complications, TNM stage and overall survival. RESULTS: The group <70 years had less comorbidities when compared with the group >70 years. Heterotopic urinary diversion was the diversion of choice in the elderly patients (97.4%). Paralytic ileus and the worsening of renal function were the only complications with statistical differences between the groups. Mean hospital length of stay was not significantly different between the groups. Younger and older patients had similar pathological staging : pT1 or less: 26,2 vs. 18.2%, pT2: 19.4 vs. 16.9%, pT3 38.8 vs. 37.7% and pT4 15.6 vs. 17.2%. Kaplan-Meier curves did not show significant differences in survival. CONCLUSIONS: Laparoscopic radical cystectomy in the elderly patient has similar rates of perioperative morbidity when compared with the younger patient and may be offered as a treatment option in selected elderly patients.